Gamification-Driven Management Information System: A Design Approach for Enhancing Students’ Final Project Supervision - Troy; Ginanjar Setyo Nugroho; Kathryn Widiyanti; Gunanto, Samuel Gandang (Journal of Information Technology and Its Utilization, 2025)
This study aims to design a gamification-based Management Information System (MIS) interface to enhance the effectiveness and engagement of students during final project supervision. The research background is based on literature findings regarding the potential of gamification in education that can encourage motivation, participation, and transparency in the learning process. The research method used is Research through Design (RtD), emphasizing the integration of gamification elements into the MIS framework, including features for recording progress, awarding points, levels, and badges related to guidance activities. The research results is a student final project MIS interface that combines managerial functions with gamification-based motivational mechanisms. This system is expected to increase student engagement, provide more transparent monitoring for supervisors, and create a more attractive and interactive guidance ecosystem. The direction of further research is directed at the development of a complete MIS prototype, limited trials, and evaluation of effectiveness through case studies.